DragonHeart : [videorecording (DVD)] a new beginning - Masterson, Chris, 1980-; Van Gorkum, Harry; Figueroa, Rona, 1972- (Rovi Media Collection., 2000)
When Geoff, an orphaned stable boy, discovers Drake, the world's last living dragon, he realizes that his dream of becoming a knight in shining armor can now come true. Together they face challenges that turn them into heroes, but they fail to see the hidden dangers that surround them.